Cerebrospinal Fluid Biomarkers in Cerebral Amyloid Angiopathy: New Data and Quantitative Meta-Analysis - Margraf, Nils G.; Jensen-Kondering, Ulf; Weiler, Caroline; Leypoldt, Frank; Maetzler, Walter; Philippen, Sarah; Bartsch, Thorsten; Flüh, Charlotte; Röcken, Christoph; Möller, Bettina; Royl, Georg; Neumann, Alexander; et al. (Frontiers in Aging Neuroscience, 2022)
Background To evaluate the diagnostic accuracy of cerebrospinal fluid (CSF) biomarkers in patients with probable cerebral amyloid angiopathy (CAA) according to the modified Boston criteria in a retrospective multicentric cohort. Methods Beta-amyloid 1-40 (Aβ40), beta-amyloid 1-42 (Aβ42), total tau (t-tau), and phosphorylated tau 181 (p-tau181) were measured in 31 patients with probable CAA, 28 patients with Alzheimer’s disease (AD), and 30 controls. Receiver-operating characteristics (ROC) analyses were performed for the measured parameters as well as the Aβ42/40 ratio to estimate diagnostic parameters. A meta-analysis of all amenable published studies was conducted. Results In our data Aβ42/40 (AUC 0.88) discriminated best between CAA and controls while Aβ40 did not perform well (AUC 0.63). Differentiating between CAA and AD, p-tau181 (AUC 0.75) discriminated best in this study while Aβ40 (AUC 0.58) and Aβ42 (AUC 0.54) provided no discrimination. In the meta-analysis, Aβ42/40 (AUC 0.90) showed the best discrimination between CAA and controls followed by t-tau (AUC 0.79), Aβ40 (AUC 0.76), and p-tau181 (AUC 0.71). P-tau181 (AUC 0.76), Aβ40 (AUC 0.73), and t-tau (AUC 0.71) differentiated comparably between AD and CAA while Aβ42 (AUC 0.54) did not. In agreement with studies examining AD biomarkers, Aβ42/40 discriminated excellently between AD and controls (AUC 0.92–0.96) in this study as well as the meta-analysis. Conclusion The analyzed parameters differentiate between controls and CAA with clinically useful accuracy (AUC > ∼0.85) but not between CAA and AD. Since there is a neuropathological, clinical and diagnostic continuum between CAA and AD, other diagnostic markers, e.g., novel CSF biomarkers or other parameters might be more successful.